(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Digital transformation has revolutionized how businesses operate and how managers lead. The integration of digital technologies into all aspects of business processes is not simply a matter of adopting new tools—it represents a fundamental shift in organizational culture, strategy, and customer engagement. In this rapidly changing environment, management strategies must evolve to remain effective and competitive. Organizations that fail to adapt risk becoming obsolete.